2019
DOI: 10.1515/ijamh-2019-0172
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of e-cigarette use among a sample of high school students in Jakarta, Indonesia

Abstract: Objectives The aim of this study was to determine the predisposing, enabling and reinforcing factors associated with electronic cigarette (e-cigarette) use among high school students in Jakarta, Indonesia. Methods This cross-sectional study took place in eight high schools in Jakarta, Indonesia. A total of 767 students were recruited by multistage cluster random sampling. Bivariate and multivariate statistical analyses were employed to determine the associations between socio-demographic, predisposing, reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 28 publications
4
34
1
Order By: Relevance
“…A systematic review of 17 studies on youth in HICs found that flavored e-cigarettes were perceived as being less harmful, lower costs, more fashionable and enjoyable taste than combustible cigarettes (Romijnders et al, 2018). Prior research shows that youth e-cigarette use is associated with male sex (Barrington-Trimis et al, 2015;Jiang et al, 2016;Park et al, 2017;Robert Lourdes et al, 2019;Soteriades et al, 2020), residence in urban areas (Park et al, 2017), low academic achievement (Kinnunen et al, 2020), poor knowledge about the harm of smoking (Jiang et al, 2016), positive attitudes toward e-cigarettes (Barrington-Trimis et al, 2015;Bigwanto et al, 2019), history of cigarette smoking (Dautzenberg et al, 2015;Jiang et al, 2016;Park et al, 2017;Bigwanto et al, 2019;Robert Lourdes et al, 2019;Xiao et al, 2019;Kinnunen et al, 2020;Soteriades et al, 2020), and friends' (Barrington-Trimis et al, 2015;Dautzenberg et al, 2015;Park et al, 2017;Xiao et al, 2019) and family's members' smoking (Barrington-Trimis et al, 2015;Dautzenberg et al, 2015;Bigwanto et al, 2019;Kinnunen et al, 2020;Soteriades et al, 2020). However, there are few studies on youth e-cigarette use in low-and middleincome countries, especially in countries that e-cigarettes are banned (Thrasher et al, 2016;Zavala-Arciniega et al, 2018;Ofuchi et al, 2020).…”
Section: Use Of E-cigarettes and Associated Factors Among Youth In Thailandmentioning
confidence: 99%
“…A systematic review of 17 studies on youth in HICs found that flavored e-cigarettes were perceived as being less harmful, lower costs, more fashionable and enjoyable taste than combustible cigarettes (Romijnders et al, 2018). Prior research shows that youth e-cigarette use is associated with male sex (Barrington-Trimis et al, 2015;Jiang et al, 2016;Park et al, 2017;Robert Lourdes et al, 2019;Soteriades et al, 2020), residence in urban areas (Park et al, 2017), low academic achievement (Kinnunen et al, 2020), poor knowledge about the harm of smoking (Jiang et al, 2016), positive attitudes toward e-cigarettes (Barrington-Trimis et al, 2015;Bigwanto et al, 2019), history of cigarette smoking (Dautzenberg et al, 2015;Jiang et al, 2016;Park et al, 2017;Bigwanto et al, 2019;Robert Lourdes et al, 2019;Xiao et al, 2019;Kinnunen et al, 2020;Soteriades et al, 2020), and friends' (Barrington-Trimis et al, 2015;Dautzenberg et al, 2015;Park et al, 2017;Xiao et al, 2019) and family's members' smoking (Barrington-Trimis et al, 2015;Dautzenberg et al, 2015;Bigwanto et al, 2019;Kinnunen et al, 2020;Soteriades et al, 2020). However, there are few studies on youth e-cigarette use in low-and middleincome countries, especially in countries that e-cigarettes are banned (Thrasher et al, 2016;Zavala-Arciniega et al, 2018;Ofuchi et al, 2020).…”
Section: Use Of E-cigarettes and Associated Factors Among Youth In Thailandmentioning
confidence: 99%
“…Results: This results of this study show that the factors that have positively associated to intentions of e-cigarettes use by adolescent are instrumental attitudes (3,035), injunctive norm (2,561), descriptive norm (4,896) and self efficacy (3,526). Experiential attitude and perceived control did not associated the intention of adolescents e-cigarette use.…”
Section: Methodmentioning
confidence: 69%
“…The sample size was determined by cluster random sampling, in 8 school which includes 291 students. Data collection was through filling out the online questionnaire and analyzed using logistic regression test to determine the association between variables.Results: This results of this study show that the factors that have positively associated to intentions of e-cigarettes use by adolescent are instrumental attitudes (3,035), injunctive norm (2,561), descriptive norm (4,896) and self efficacy (3,526). Experiential attitude and perceived control did not associated the intention of adolescents e-cigarette use.…”
mentioning
confidence: 69%
See 2 more Smart Citations